If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x+19=7x+13
We move all terms to the left:
15x+19-(7x+13)=0
We get rid of parentheses
15x-7x-13+19=0
We add all the numbers together, and all the variables
8x+6=0
We move all terms containing x to the left, all other terms to the right
8x=-6
x=-6/8
x=-3/4
| -6(j+-8)=66 | | 40x=100+15× | | 2(11–a)=a–5 | | 3/4n-18=n/4-4 | | 59+(3x+4)+6x=180 | | -10-6k+2-3k=-8+k | | Y*(y-1)=11 | | (8x+7)=(2x+10) | | h7.5=-3.2 | | 3(y+3)+y=2(y-1)+9 | | 45x=185 | | 2x+6x-4=-12 | | C(c-1)=11 | | 4x2+24x-8=0 | | 8h-5=29 | | 4n+14=n+62 | | 23x-5+22x=180 | | -6-3-2p-8=2p-5 | | x−5x=−20 | | 3-5p+1-5(40-p)=0 | | 8h5=29 | | 8(a-95+16=32 | | 12/x=x/6 | | -4d+11=35 | | 7^4x-5=49 | | 20w-18w=14 | | 0.34y=18 | | X+32+2x-17=180 | | 4(q-76-4=8 | | t/4+-10=-5.9 | | 1/4n=17 | | .6+w=4 |